Paid vacation use: The role of works councils - Laszlo Goerke; Sabrina Jeworrek (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2016)
We investigate the relationship between co-determination at the plant level and paid vacation in Germany. From a legal perspective, works councils have no impact on vacation entitlements, but they can affect their use. Employing data from the German Socio-Economic Panel (SOEP), we find that male employees who work in an establishment, in which a works council exists, take almost two additional days of paid vacation annually, relative to employees in an establishment without such institution. The effect for females is much smaller, if discernible at all. The data suggests that this gender gap might be due to the fact that women exploit vacation entitlements more comprehensively than men already in the absence of a works council.
Keywords: J22; J32; J33; J53; M54; 330; Gender Difference; German Socio-Economic Panel (SOEP); Paid Vacation; Works Council